SPE/DOE Improved Oil Recovery Symposium 1994
DOI: 10.2118/27798-ms
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Foam Field Verification Pilot Test at EVGSAU: Phase IIIC—Reservoir Characterization and Response to Foam Injection

Abstract: Thie paper was preperad for presentation et the SPHJOE Ninth Symposium on Improved Oil Recovery held in Tulsa, Oklahoma, U. S.A.,17-20 April 1S94. Thie paper wee se!ectad for presentation by an SPE Program Cemmiftss fellowing review of information conteinsd in en abstraof aubmiffed by the fruiiroii~). COfitefiiS of % pai%i, ss PfeaentSd, have not @n reviewed by theSociety of PetroIaum Engineers and are aubjecf to corraotion by the author(a). The materiel, cc presented, does not neceeaarily reflect any poaRion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…There are a number of subsurface applications that utilize gas injection, such as enhanced oil recovery (EOR), aquifer remediation, and hydraulic fracturing [1][2][3][4][5][6][7][8][9][10][11] . However, the efficiency of these applications is limited due to the high mobility of gas, which results in problems like viscous fingering and gravity override 12 .…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of subsurface applications that utilize gas injection, such as enhanced oil recovery (EOR), aquifer remediation, and hydraulic fracturing [1][2][3][4][5][6][7][8][9][10][11] . However, the efficiency of these applications is limited due to the high mobility of gas, which results in problems like viscous fingering and gravity override 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory results showed that Chaser TM CD1045 was an effective foaming agent at reservoir conditions for EVGSAU cores. 21 The field trial at EVGSAU [22][23][24][25] confirmed these findings. The surfactant showed great effectiveness as a CO 2 mobility reduction agent.…”
mentioning
confidence: 76%
“…A comparison between pressure drop during SAG injection and co-injection modes showed that the pressure drop during surfactant/CO 2 co-injection is 2-10 times higher than for CO 2 following surfactant solution injection 26,41 mode. Therefore, when SAG mode is used in the field, smaller values are to be employed in the design of the field process.…”
Section: Adapting Laboratory Testing Approaches To the Field Needsmentioning
confidence: 98%
“…The East Vacuum Grayburg-San Andres Unit (EVGSAU) pilot [23][24][25][26] is the second most successful foam field test to date. This pilot was based on an extensive amount of laboratory work, and it was by far the best instrumented field pilot.…”
Section: High Pressure Foam Application: Gasmentioning
confidence: 99%